Pengelolaan Sampah pada Pondok Pesantren Al-Muhajirin, Jayamukti, Bekasi, Provinsi Jawa Barat - Windi, Windi; Aguswin, Ahmad; Akromusyuhada, Akhmad; Argiyan Syah, Dika (Lembaga Kajian Demokrasi dan Pemberdayaan Masyarakat (LKD-PM), 2023)
Community service activities carried out at the Al-Muhajirin Islamic boarding school, Bekasi Regency are a form of concern for the environment in the Islamic boarding school area. The waste produced by the Al-Muhajirin Islamic boarding school has not yet been processed, but is immediately collected and thrown away. In the waste collection process, comfort problems often occur, especially from waste pollution which produces unpleasant odors. This is potentially due to a lack of concern/awareness among students regarding waste processing in the Islamic boarding school environment. To overcome this problem, service activities are carried out through training for students regarding environmental concern/awareness based on a waste management system. The training is carried out inside and outside the classroom, in the form of sorting the waste produced and then continuing with waste processing and its economic potential. Waste processing practices that have economic value are carried out to foster insight and develop an entrepreneurial spirit. This activity process also creates comfort and produces a cleaner environment because there is no accumulation of rubbish in the Islamic boarding school environment.a